Sir Cumference and the first round table : a math adventure - Neuschwander, Cindy; Geehan, Wayne (Watertown, MA : Charlesbridge, 1997)
A math adventure in which King Arthur finds the perfect shape for his table with the ideas of his wife and son, and the assistance of his knight, Sir Cumference.
Book Links (A.L.A.).
4.8.
4.8
3-6
Keywords: Geometry -- Juvenile literature; Geometry; Shape; Geometry; Shape